Vocational High School English Teachers’ Perspectives On “Merdeka Belajar” Curriculum - Anita Kusuma Pertiwi; Ririn Pusparini (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
This study aims to identify the teachers’ perspectives on the Merdeka Belajar curriculum in terms of its concept and lesson plan. The method used was qualitative-descriptive that involved 8 English teachers from different Vocational High Schools in Surabaya. The data collected through questionnaires and semi-structured interviews. After being analyzed, the results showed that not all teachers understand the concept of Merdeka Belajar. The finding also showed that the implementation of a one-page lesson plan (RPP 1 Lembar) had not met the expectation of Merdeka Belajar. What was being stated by participants was different from what was being told during the interview and this affects the final results.  However, all participants fully support the implementation of this new curriculum